Cost‐Effectiveness of Surgical Weight‐Loss Interventions for Patients With Knee Osteoarthritis and Class III Obesity. Issue 3 (17th November 2022) - Kostic, Aleksandra M.; Leifer, Valia P.; Gong, Yusi; Robinson, Malcolm K.; Collins, Jamie E.; Neogi, Tuhina; Messier, Stephen P.; Hunter, David J.; Selzer, Faith; Suter, Lisa G.; Katz, Jeffrey N.; Losina, Elena
Abstract : Objective: Class III obesity (body mass index [BMI] ≥40 kg/m 2 ) is associated with worse knee pain and total knee replacement (TKR) outcomes. Because bariatric surgery yields sustainable weight loss for individuals with BMI ≥40 kg/m 2, our objective was to establish the value of Roux‐en‐Y gastric bypass (RYGB) and laparoscopic sleeve gastrectomy (LSG) in conjunction with usual care for knee osteoarthritis (OA) patients with BMI ≥40 kg/m 2 . Methods: We used the Osteoarthritis Policy model to assess long‐term clinical benefits, costs, and cost‐effectiveness of RYGB and LSG. We derived model inputs for efficacy, costs, and complications associated with these treatments from published data. Primary outcomes included quality‐adjusted life‐years (QALYs), lifetime costs, and incremental cost‐effectiveness ratios (ICERs), all discounted at 3%/year. This analysis was conducted from a health care sector perspective. We performed sensitivity analyses to evaluate uncertainty in input parameters. Results: The usual care + RYGB strategy increased the quality‐adjusted life expectancy by 1.35 years and lifetime costs by 7, 209, compared to usual care alone (ICER = 5, 300/QALY). The usual care + LSG strategy yielded less benefit than usual care + RYGB and was dominated. Relative to usual care alone, both usual care + RYGB and usual care + LSG reduced opioid use from 13% to 4%, and increased TKR usage from 30% to 50% and 41%, respectively. For cohorts with BMI between 38 and 41 kg/m 2, usual care + LSG dominated usual care + RYGB. In the probabilistic sensitivity analysis, at a willingness‐to‐pay threshold of 50, 000/QALY, usual care + RYGB and usual care + LSG were cost‐effective in 70% and 30% of iterations, respectively. Conclusion: RYGB offers good value among knee OA patients with BMI ≥40 kg/m 2, while LSG may provide good value among those with BMI between 35 and 41 kg/m 2 .